(3aGYdjI HQfGeL faS MQci ai JMSjf HYV GdeJZjQGJ GdSdhcjI GdeYQajI dOi JdGejP GdSefI GdeaQWI h GdfMGaI Phi UYhHGJ GdJYde (B/ s - (3efUhQ YHOGdhgGH CMeO GdMHTis; (3CeGfi SYjOI SjO EHQGgje (B: s; (3SejQI CHhGdMSf YHOGdSdGe (B: s; (3SgG eMeO acQi (B: s ((3GdbGgQI (B: s (3efUhQ YHOGdhgGH CMeO GdMHTi (B: s, 2020)
(3gOaJ GdOQGSI Edi GdJYQa Ydi CKQ HQfGeL faS MQci ai JMSjf HYV GdeJZjQGJ GdSdhcjI h GdeYQajI dOi JdGejP GdSefI GdeaQWI h GdfMGaI Phi UYhHGJ GdJYde(B: (3h bO Je GNJjGQ YjfI YOOgG (B(20) (3Wad h WadI ef eLehYI eOGQS GdJYdje GdCSGSi (B((3GdGHJOGFi h GdEYOGOi(B) (3GdJGHYI dEOGQI GdSfWI GdJYdjejI (B- (3eOjQjI GdJQHjI h GdJYdje HGdZQHjI, h JJQGhM CYeGQge Hjf (B(11: 14) (3SfI, h bO Je JbSjege Edi CQHY eLehYGJ(B: (3eLehYI GdPchQ Phj SefI eaQWI h YOOgG (B(5) (3CWaGd(B: (3eLehYI GdPchQ Phi fMGaI RGFOI h YOOge (B(5) (3CWaGd(B: (3eLehYI GdEfGK PhGJ SefI eaQWI h YOOgf (B(5) (3CWaGd(B: (3eLehYI GdEfGK PhGJ fMGaI RGFOI h YOOgf (B(5) (3CWaGd, h dJMbjb CgOGa GdOQGSI GSJNOe GdHGMK eLehYI ef GdCOhGJ HYO GdJMbb ef eDTQGJ UObgG h KHGJgG MjK Je GSJNOGe ebjGS GVWQGH UhQI GdLSe (B((3EYOGO(B: (3eLOi eMeO GdOShbi(B): (3ebjGS eDTQ cJdI GdLSe ddSefI h GdfMGaI (B((3GdeYgO Gdbhei GdCeQjci ddUMI h efXeI GdUMI GdYGdejI(B): (3GSJeGQI HjGfGJ ChdjI Yf Phi GdSefI GdeaQWI hGdfMGaI GdRGFOI (B((3EYOGO GdHGMK(B): (3HWGQjI bjGS UYhHGJ GdJYde (B((3EYOGO(B: (3aJMi eUWaj GdRjGJ(B): (3HQfGeL GdOQGSI h gh NWI JOQjHjI bUjQI GdeOi TGedI GdCOhGJ h GdedGYH GdeYOI dgPG GdZQV EYOGO GdHGMKs
(3GWQhMI (B((3OcJhQGg(B) - (3LGeYI GdbGgQI (B- (3cdjI GdOQGSGJ GdYdjG ddJQHjI (B- (3bSe GdJQHjI GdNGUIs
(3UOQ GjVG cbQU eOeLs
Keywords: (3GdCWaGd Phh UYhHGJ GdJYdes; (3GdSefI GdeaQWIs; (3UhQI GdLSes